Development of an MRI-compatible digital SiPM detector stack for simultaneous PET/MRI - Düppenbecker, Peter M (Biomed Phys Eng Express, 2016)
Advances in solid-state photon detectors paved the way to combine positron emission tomography (PET) and magnetic resonance imaging (MRI) into highly integrated, truly simultaneous, hybrid imaging systems. Based on the most recent digital SiPM technology, we developed an MRI-compatible PET detector stack, intended as a building block for next generation simultaneous PET/MRI systems. Our detector stack comprises an array of 8 × 8 digital SiPM channels with 4 mm pitch using Philips Digital Photon Counting DPC 3200-22 devices, an FPGA for data acquisition, a supply voltage control system and a cooling infrastructure. This is the first detector design that allows the operation of digital SiPMs simultaneously inside an MRI system. We tested and optimized the MRI-compatibility of our detector stack on a laboratory test bench as well as in combination with a Philips Achieva 3 T MRI system. Our design clearly reduces distortions of the static magnetic field compared to a conventional design. The MRI static magnetic field causes weak and directional drift effects on voltage regulators, but has no direct impact on detector performance. MRI gradient switching initially degraded energy and timing resolution. Both distortions could be ascribed to voltage variations induced on the bias and the FPGA core voltage supply respectively. Based on these findings, we improved our detector design and our final design shows virtually no energy or timing degradations, even during heavy and continuous MRI gradient switching. In particular, we found no evidence that the performance of the DPC 3200-22 digital SiPM itself is degraded by the MRI system.